Contemporary theories of liberalism : public reason as a post-Enlightenment project - Gaus, Gerald F. (London ; Thousand Oaks, Calif. : SAGE, 2003)
In this text, Gerald F. Gaus provides students with a comprehensive overview of the key tenets of liberalism developed through Hobbes, Locke, Kant and Rawls to present day theories and debates.
Cover -- Summary of Contents -- Contents -- List of Figures -- Preface -- Chapter 1 -- Liberalism and Reason -- Chapter 2 -- Pluralistic Liberalism: Making Do Without Public Reason? -- Chapter 3 -- Hobbesian-inspired Liberalism: Public Reason Out of Individual Reason -- Chapter 4 -- Collective Reason: Deepening the Social Roots of Public Reason -- Chapter 5 -- Deliberative Democracy: Public Reason and Political Consensus -- Chapter 6 -- Political Democracy: Public Reason Through Aggregation -- Chapter 7 -- Rawls's Political Liberalism: Public Reason as the Domain of the Political -- Chapter 8 -- Justificatory Liberalism and Adjudicative Democracy: Public Reason and Umpiring.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Liberalism; Free enterprise; Libéralisme.; liberalism; POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism; Free enterprise; Liberalism; Liberalismus; Liberalisme; Theorieën.